Analysis of Interrupted SFCW Radar Data Corresponding to Living Targets Behind Obstruction - Fidan, Buse Nur; Oz, Fikriye; Akinci, Mehmet Nuri; Baykut, Suleyman (IEEE, 2024)
Radar systems have various applications, and it is observed that these systems are frequently preferred in the field of through-wall imaging. In this study, data obtained from a living target behind a 50 cm thick concrete wall using Stepped Frequency Continuous Wave (SFCW) radar are examined. The first experiment dataset contains only the breathing movements of the target, while the second experiment dataset includes both the breathing data and irregular movements of the target's arms. To mitigate the significant drawbacks of continuous wave radars, such as direct coupling and initial reflection effects, a switching structure is employed in the transmitter and receiver channels. The acquired interrupted SFCW radar data are analyzed using various signal processing methods, and the results are evaluated.